The Role of a Notary in Making A Syndicated Loan Authentic Deed - Jodi Purgito; Bambang Tri Bawono (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this research is to analyze & find out: 1). The role of the Notary in the implementation of the authentic deed of syndicated loan (syndicated loan) 2). Barriers & solutions in making authentic syndicated credit deeds. The approach method in this research is a sociological juridical approach. The data used are primary & secondary data obtained through interviews & literature study, data analysis was carried out by analytical descriptive. The results of the research concluded: 1). The role of the Notary in the implementation of the authentic deed of syndicated loan (syndicated loan) includes, among others, making a deed of a syndicated credit agreement requested by the bank, providing guidance to the bank regarding credit documents, making final credit documents, confirm the data to the bank if there are things that are not or are not clear, keep the name of the debtor & the amount of credit requested, & enter it into the register book to be registered with the district court. 2) Obstacles & solutions in Making Authentic Deeds for Syndicated Loans, namely: difficulties in making authentic deeds before a Notary at the same time & place, dual duties & problems with guarantee institutions. The solution that can be done to overcome these obstacles is that the Notary should add HR in his office to help the Notary's tasks, the bank must also add HR, so that there is no double duty. To deal with problems related to guarantee institutions, the Paripassu Security Sharing Agreement (Security Sharing Agreement) emerged.